Analisis Loyalitas Kerja Karyawan pada PT. XYZ - Maulhika Putri Winaryanti; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (OPTIMAL Jurnal Ekonomi dan Manajemen, 2024)
Employee job loyalty is one of the crucial issues in today's corporate world. Many companies face challenges in keeping their employees loyal and committed to their work. The aim of this research is to understand the job loyalty of employees at PT. XYZ across various departments. This study utilizes a qualitative descriptive approach, relying on both primary and secondary data. The research sample consists of 4 individuals chosen through non-purposive sampling method. From the results, it's evident that job loyalty among employees at PT. XYZ is quite high, with employees prioritizing the company's interests over personal ones. However, age and generational differences do influence the employees' dedication levels. Factors affecting loyalty include a strong relationship between the company and its employees, employee welfare, management support, and fair compensation. The company has implemented comprehensive policies supporting employee loyalty, such as a transparent performance assessment system, clear career policies, and a commitment to retain employees during difficult situations. The research findings highlight that understanding these factors is pivotal in maintaining and enhancing employee loyalty in the future. This study offers insights for companies to improve employee job loyalty, thereby positively impacting overall company performance and sustainability.